Construction of VMI Mode Supply Chain Management System Based on Block Chain - Wang, Jinlong; Liu, Jing; Zheng, Lijuan (Algorithms and Architectures for Parallel Processing, 2018)
Block chain has become a hot research topic in recent years, such as the United Nations, the International Monetary Fund and other international organizations, as well as many governments. Industry has also increased investment efforts. At present, the application of block chain has been extended to the Internet of things, intelligent manufacturing, supply chain management, digital asset trading and other fields, which will bring new opportunities for the development of cloud computing, big data, mobile Internet and other new generation of information technology. On the basis of analyzing the disadvantages of the traditional VMI mode, this paper discusses the feasibility of applying the block chain technology in the VMI mode supply chain, and tries to construct the VMI mode supply chain management system based on the block chain technology. The purpose of this paper is to combine the blockchain technology and supply chain management in order to find a feasible way to implement the VMI supply chain mode.